Algunas características Epidemiológicas de la Gestante con infección urinaria en el Hospital II IPSS Tarapoto Período. Enero - Diciembre 1994 - García Pinchi, Jeny del Carmen (1995)
Urinary tract infection is a clinical or histopathologic state as a direct result of bacterial colonization in tissues of any part of the urinary tree. (2) This study applied correlational design was performed in the hospital IPSS Tarapoto II, during the year 1994 in order to determine the epidemiological characteristics of pregnant women with urinary tract infection. Our study sample consisted of 181 women with pathological result of urinary sediment, in which after the short preparation and guidance urine sample was selected to perform the respective urine culture. After analysis and processing of data found that 36.5% percent of the patients studied had positive urine culture and 63.5% percent had negative urine culture. The parity and maternal history of abortion and vaginitis were factors associated with urinary tract infection. The most common uropathogens were isolated: Escherichis E1 coli with 22.1 percent, Estaphylococcue SD, with 6.4 percent, Klebsiella SD, with 4.4 percent. Complications occurred more frequently in women with positive urine culture were: Preterm 22.6 percent premature rupture of membranes with 7.6 percent, preterm labor with 8.1 percent and threatened abortion with 4.5 percent.